Aphis (Hemiptera: Aphididae) species groups found in the Midwestern United States and their contribution to the phylogenetic knowledge of the genus. (15th January 2014) - Lagos, Doris M.; Voegtlin, David J.; Coeur d'acier, Armelle; Giordano, Rosanna
Abstract A phylogeny of the genus Aphis Linnaeus, 1 758 was built primarily from specimens collected in the Midwest of the United States. A data matrix was constructed with 68 species and 41 morphological characters with respective character states of alate and apterous viviparous females. Dendrogram topologies of analyses performed using UPGMA (Unweighted Pair Group Method with Arithmetic Mean), Maximum Parsimony and Bayesian analysis of Cytochrome Oxidase I, Elongation Factor 1‐α and primary endosymbiont Buchnera aphidicola 16S sequences were not congruent. Bayesian analysis strongly supported most terminal nodes of the phylogenetic trees. The phylogeny was strongly supported by EF1‐α, and analysis of COI and EF1‐α molecular data combined with morphological characters. It was not supported by single analysis of COI or Buchnera aphidicola 16S. Results from the Bayesian phylogeny show 4 main species groups: asclepiadis, fabae, gossypii, and middletonii. Results place Aphis and species of the genera Protaphis Börner, 1952, Toxoptera Koch, 1856 and Xerobion Nevsky, 1928 in a monophyletic clade. Morphological characters support this monophyly as well. The phylogeny shows that the monophyletic clade of the North American middletonii species group belong to the genus Protaphis: P. debilicornis (Gillette & Palmer, 1929), comb. nov., P. echinaceae (Lagos and Voegtlin, 2009), comb. nov., and P. middletonii (Thomas, 1879). The genus Toxoptera should be considered a subgenus of Aphis (stat. nov.). The analysis also indicates that the current genus Iowana Frison, 1954 should be considered a subgenus of Aphis (stat. nov.).